2011
DOI: 10.1051/0004-6361/201117121
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking atomic data for astrophysics: Fe xiii EUV lines

Abstract: Recent atomic data for Fe xiii are benchmarked against high-resolution spectroscopic observations of the solar corona. All the identifications of the EUV lines are reviewed by also taking into account laboratory measurements. A few new identifications are proposed, and many wavelengths are revised. All the strongest EUV lines are now identified. Very good agreement between predicted and observed line intensities is generally found using the latest atomic calculations. We clearly indicate which EUV lines are bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Vilkas & Ishikawa (2004) presented ab-initio atomic structure calculations, and suggested that in several cases misidentifications have occurred. The energies of the lower n = 3 levels have been carefully assessed in Del Zanna (2011) and are adopted here. Fig.…”
Section: Fe XIIImentioning
confidence: 99%
“…Vilkas & Ishikawa (2004) presented ab-initio atomic structure calculations, and suggested that in several cases misidentifications have occurred. The energies of the lower n = 3 levels have been carefully assessed in Del Zanna (2011) and are adopted here. Fig.…”
Section: Fe XIIImentioning
confidence: 99%
“…In Table 8, the computed excitation RMCDHF/RCI energies are compared with observed energies from Del Zanna [57], as well as with energies by Vilkas and Ishikawa [58] using the MRMP method. The mean deviation is 0.076% for RMCDHF/RCI and only 0.034% for MRMP.…”
Section: Sequence Ionsmentioning
confidence: 99%
“…Comparison of calculated and observed excitation energies in cm −1 . E RCI RMCDHF/RCI energies from [56], E MRMP MRMP energies from [58] and E DZ observed energies from [57]. Relative errors in % for the calculated energies are shown in parenthesis.…”
Section: Sequence Ionsmentioning
confidence: 99%
“…It must be mentioned that cohesiveness between atomic data producers and users has not been easy to broker in the past, in spite of periodic international conferences such as ICAMDATA [37], joint symposia (e.g., the Tenerife meeting in October 2010 on "Uncertainties in atomic data and how they propagate in chemical abundances" [38,39]), capacity development schools (e.g., NebulAtom [40]), and the AstroAtom blog [41]. However, there are exceptions to this inherent detachment, in particular the extensive astrophysical benchmarks that have been carried out of iron EUV and X-ray lines for the CHIANTI database [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. …”
Section: Virtual Research Communitiesmentioning
confidence: 99%